Gene expression in Kinetoplastids - Clayton-Gouthro, Cecile M. (Current opinion in microbiology, 2016)
Kinetoplastid parasites adapt to different environments with wide-reaching control of gene expression, but transcription of nuclear protein-coding genes is polycistronic: there is no individual control of transcription initiation. Mature mRNAs are made by co-transcriptional trans splicing and polyadenylation, and competition between processing and nuclear degradation may contribute to regulation of mRNA levels. In the cytosol both the extent to which mRNAs are translated, and mRNA decay rates, vary enormously. I here highlight gaps in our knowledge: no measurements of transcription initiation or elongation rates; no measurements of how, precisely, mRNA processing and nuclear degradation control mRNA levels; and extremely limited understanding of the contributions of different translation initiation factors and RNA-binding proteins to mRNA fate.